2021
DOI: 10.3390/polym13224026
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of the Buffer Capacity of Various Types of Polyelectrolyte Microcapsules

Abstract: Polyelectrolyte microcapsules, which are obtained by the method of alternate adsorption of oppositely charged polyelectrolytes onto colloidal particles of micron size, are widely used in science and industry. Nevertheless, the properties of microcapsules are still poorly understood. In particular, there is no information in the literature on the buffer capacity. However, information on the presence of a buffer capacity and an understanding of its mechanisms can both simplify the use of microcapsules and expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Additionally, we found the dependence of the buffer capacity’s behavior on the PMC shell’s composition, the presence of an encapsulated protein, the magnitude of ionic strength, and the temperature of the solution. These studies demonstrated that the buffer properties of microcapsules are determined by the charged regions of PAH (uncompensated with PSS) in the composition of their shell [ 2 , 9 ]. However, as described above, the number and density of PAH charged groups (distance between nearest groups of -NH 3 + groups) also depend on the number of microcapsule shell layers and the number of microcapsules themselves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we found the dependence of the buffer capacity’s behavior on the PMC shell’s composition, the presence of an encapsulated protein, the magnitude of ionic strength, and the temperature of the solution. These studies demonstrated that the buffer properties of microcapsules are determined by the charged regions of PAH (uncompensated with PSS) in the composition of their shell [ 2 , 9 ]. However, as described above, the number and density of PAH charged groups (distance between nearest groups of -NH 3 + groups) also depend on the number of microcapsule shell layers and the number of microcapsules themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Polyelectrolytes and their complexes can change the degree of their (de) protonation and charge density when the pH of the solution changes. A polyelectrolyte microcapsule shell consisting of polyelectrolyte complex will have buffer capacity, too [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we revealed the presence of a buffer capacity (BC) in PMCs consisting of PAH and PSS [ 12 ]. It was also found that BC microcapsules increase in the presence of salt in the pH range 5.5 to 9, and it was hypothesized that BC microcapsules correspond to unpaired sections of PAH in their composition.…”
Section: Resultsmentioning
confidence: 99%
“…Dubrovskii et al have already demonstrated differences in the behavior of the buffer capacity of polyelectrolyte microcapsules depending on the composition of the PMC shell, the presence of an encapsulated protein, and 0.5 M sodium chloride [ 12 ]. We assume that the buffer capacity of PMCs can also be affected by the magnitude of the ionic strength and the temperature of the solution, because there are several works describing their influence on the buffer capacity of free polyelectrolytes and their complexes [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%